Development, Validation and Approbation Analytical Method for the Quantitative Determination of Taurine by HPLC-UV Method in the Test of Comparative Dissolution Kinetics - A. M. Poluyanov; A. Kochug; L. S. Mitrofanova; I. D. Nikitin; O. Yu. Vergasov; I. E. Shohin; E. N. Fisher (Разработка и регистрация лекарственных средств, 2023)
Introduction. Taurine is a non-proteinogenic amino acid. The molecule is involved in lipid metabolism, adsorbs fat-soluble vitamins, and its conjugates with bile acids contribute to the emulsification of fats in the intestine. Drugs, which include a taurine molecule, have anti-cataract, cardiotonic, metabolic effects, and also stimulate regeneration. Among the dosage forms, where taurine acts as an active substance, there is a solid dosage form – film-coated tablets. One of the methods for assessing the quality of solid dosage forms is a comparative dissolution kinetics test. High-performance chromatography with ultraviolet detection is a widely used method for quantification within the dissolution test, however, for taurine, which does not contain chromophore groups in its structure, this method is not directly applicable. To solve this problem, one can apply the method of pre-column derivatization, because of which an fragment is introduced into the structure, providing a bathochromic shift in the UV spectrum of the starting compound.Aim. Development, validation and approbation analytical method for the quantitative determination of taurine by high-performance chromatography with ultraviolet detection as part of a test comparative kinetics dissolution of taurine tablets with a dosage of 250 and 500 mg.Materials and methods. The following preparations were used for the analysis: taurine tablets, film-coated 250 mg and 500 mg, domestic production with a valid expiration date. The comparative dissolution kinetics test was carried out on a DT 126 Light instrument for the "Dissolution" test (ERWEKA GmbH, Germany). Chromatographic separation and detection were performed on a Nexera-i LC-2040 high-performance liquid chromatograph (Shimadzu Corporation, Japan) equipped with a column and sample thermostat, a degasser, an autosampler, and an ultraviolet detector. Detection was carried out at a wavelength of 254 nm after derivatization of the taurine molecule with 4-toluenesulfonyl chloride. Were used a Shim-pack Velox C18 5 μm 4.6 × 150 mm column (Shimadzu Corporation, Japan) and a Shim-pack Velox C18 EXP Guard Column Cartridge 5 μm 4.6 × 5 mm (Shimadzu Corporation, Japan). Primary data were processed using LabSolutions Single LC software (Shimadzu Corporation, Japan).Results and discussion. The optimal conditions for taurine derivatization have been selected, and a method for the quantitative determination of taurine by HPLC-UV in test comparative kinetics dissolution in three dissolution media: 0.1 M hydrochloric acid solution with pH 1.2, acetate buffer solution with pH 4.5, phosphate buffer solution with pH 6.8, as well as in the quality control medium – purified water has been developed and validated. During the validation of the developed methodology, it was found that the validation characteristics are within the acceptance criteria in 4 dissolution media. The analytical range of the method was 0.05–1.2 mg/mL and allows the developed method to be used for the quantitative determination of tablets with a dosage of 250 mg and 500 mg as part of the test comparative kinetics dissolution. The method was tested in 4 dissolution media, in all media, there was a complete release in both dosages (more than 85 % by 30 minutes).Conclusion. The method was tested in three dissolution media: 0.1 M hydrochloric acid solution with pH 1.2, acetate buffer solution with pH 4.5, phosphate buffer solution with pH 6.8, as well as in the quality control medium – purified water. In all media, there was a complete release in both dosages (more than 85 % by 30 minutes).